(untitled) - Hutchinson, Sarah E. (Boston, MA., 2000)
Designed for the introduction to computers or computer literacy course found in the business or CIS department at two-year and four-year schools.
Keywords: Computers,Information technology,Máy tính,Công nghệ thông tin